Acetylcholinesterase and butyrylcholinesterase activity in the cerebrospinal fluid of patients with neurodegenerative diseases involving cholinergic systems. Issue 5 (May 1987) - Ruberg, M; Villageois, A; Bonnet, A M; Pillon, B; Rieger, F; Agid, Y
Abstract : Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were assayed in the cerebrospinal fluid (CSF) of subjects with neurodegenerative diseases (dementing and non-dementing, with and without known cholinergic lesions), to determine whether CSF AChE is a valid marker of central cholinergic activity. The relative proportions of the different forms of each enzyme and of AChE to BChE were similar in CSF and brain. AChE decreased in Huntington's chorea (degeneration of striatal cholinergic interneurons) but also in multiple sclerosis (not known to affect cholinergic systems). BChE paralleled AChE, although the enzymes were dissociated in some patients. It is concluded that CSF AChE activity may globally reflect brain AChE, but pathology-induced changes may not be directly reflected.